Da'wah Communication Management Through Leadership Culture at PT. Sygma Examedia Arkanleema - Wahyudi, Ira; Suhendi, Hendi; Luthfiyyah, Annisa; Anggraini, Ine (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The growth of leadership styles is triggered by one of the important roles of organizational culture. Leadership found that it can have a positive impact on improving employee performance. The task of a leader is to build an organizational culture to make it easier for the company to achieve its stated vision and mission. Organizational culture has the meaning of a structured pattern of behavior, consisting of language, thoughts, actions, habits, rules and principles. Various views on leadership from an Islamic perspective that occur in several institutions or companies as workplaces make the author interested. to examine the leadership style in the Syaamil Quran in deeper Islamic concepts. The aim of this study is to find out more about the habits carried out in companies that adhere to Islamic values, as well as looking at the organizational culture in the work environment at the Syaamil Quran company. This study approach uses documentation and text. According to Sujarweni, document study is written documentary material, which can be in the form of textbooks, newspapers, magazines, letters, films, diaries, manuscripts, articles and the like. However, in the context of this study, the author uses book and journal references as well as interviews. Data collection was carried out using reference data related to Islamic leadership.